A self-sensing vibrotactile transducer for bidirectional tactile interaction - Davison,M; McPherson,A (Springer, 2024)
An approach to achieving simultaneous, collocated vibrotactile haptic feedback and tactile sensing is presented. A single voice coil transducer is used for sensing transients such tap strikes and taps by a fingertip, along with continuous surface pressure. A current drive amplifier provides the actuation signal. A digital filter configuration is used to cancel the actuation signal from the voltage sensing signal by modelling the transducer’s impedance. The possible benefits of the system within digital musical instrument (DMI) design are briefly discussed.